The Kaddu Wasswa archive : a visual biography - Stultiens, Andrea; Kisitu, Arthur C.; Kaddu Wasswa, John. (Rotterdam : Post Editions, 2010)
The Kaddu Wasswa archive by photographer Andrea Stultiens is the visual biography of Ugandan John Kaddu Wasswa, born in 1933, who played a an important role in his community as a teacher and social worker. What is exceptional about the now 77-year old Kaddu Wasswa is that he has always documented his activities. He wrote novels, plays and essays, took photographs and collected photos. Additionally, his extensive archive contains letters and newspaper clippings, often with added commentary. Andrea Stultiens met Kaddu Wasswa in 2008 through his grandson, photographer Arthur C. Kisitu. Together, Stultiens and Kisitu set out to explore Kaddu Wasswa's archive. She took photographs of the documents to which she added her and Kisitu's own photos which were taken during their meetings. The result is a unique biography in which the author is personally visible as well. Exhibition: Nederlands Fotomuseum, Rotterdam (30.10.2010-2.01.2011).
Folded sheet contains a keyword index, records list, and timelines; tipped-in.
boek
Keywords: Kisitu, Arthur C; Stultiens, Andrea; Kaddu Wasswa, John